2017
DOI: 10.3892/or.2017.5629
|View full text |Cite
|
Sign up to set email alerts
|

Nifuroxazide prompts antitumor immune response of TCL-loaded DC in mice with orthotopically-implanted hepatocarcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly aggressive malignancy with a poor prognosis and high mortality. At present, vaccination with tumor cell lysate (TCL) loaded dendritic cells (DC) has been shown to be an effective therapy against HCC. However, the ability of promoting the specific T cell immune response is rather weak, influencing the antitumor response. Thus, it is necessary to find a strategy to improve the antitumor effect of TCL-loaded DC. Activation of signal transducer and activator of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The current treatment of melanoma is based on surgery plus chemotherapy or radiation therapy; however, even dacarba-zine, the standard first-line treatment for melanoma, does not improve the overall survival benefit ( 2 ). Previous studies have reported that numerous Food and Drug Administration (FDA)-approved drugs may be useful as novel pharmacotherapies in the treatment of malignant tumours ( 3 6 ). Consequently, additional novel drugs need to be identified to suppress cancer cell growth, diversify options and enhance the effectiveness of antitumour therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment of melanoma is based on surgery plus chemotherapy or radiation therapy; however, even dacarba-zine, the standard first-line treatment for melanoma, does not improve the overall survival benefit ( 2 ). Previous studies have reported that numerous Food and Drug Administration (FDA)-approved drugs may be useful as novel pharmacotherapies in the treatment of malignant tumours ( 3 6 ). Consequently, additional novel drugs need to be identified to suppress cancer cell growth, diversify options and enhance the effectiveness of antitumour therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In these activities, the blocking of the STAT3 pathways plays an important role. Nifuroxazide can be effective as prophylaxis or second-line therapy for aGvHD (4)(5)(6)(7)(8)(28)(29)(30). It can be assumed that this old drug will find a new application in medicine.…”
Section: Resultsmentioning
confidence: 99%
“…STAT3 inhibitors, including AZD9150 and TTI-101, have entered the clinical trial phase for HCC treatment (ClinicalTrials.gov identifier: NCT03195699 and NCT01839604, respectively). Several drugs, which were not initially applied for tumor treatment, have also been found to exert anticancer effects by blocking STAT3[58-60]. Thus, the identification of new STAT3-targeted inhibitors is still an important direction for drug development.…”
Section: Molecular Mechanisms Underlying Hccmentioning
confidence: 99%